Pershing's Crusaders : The American Soldier in World War I - Faulkner, Richard Shawn (Book collections on Project MUSE., 2017)
"The most systematic, comprehensive, detailed, and up-to-date study yet published of the experiences, daily life, and representative attitudes of the American soldier (Army & Marine) in World War I. It will be a seminal source for anyone interested in the World War I-era American army and/or the history of early twentieth-century America"--Publisher